Evaluating the Performance of Excavator Plows Equipped With Smart Systems to Improve Plowing Efficiency - Mohsin , Yahya Y. (American Journal of Botany and Bioengineering, 2026)
This exploration aims to estimate the performance of excavator plows equipped with smart systems grounded on detector and automatic control technologies, and their part in perfecting furrowing effectiveness, reducing energy consumption, and adding productivity in agrarian operations. The study was conducted on three different models of plow harrows, one of which was conventional, another equipped with a GPS system, and the third equipped with an automatic detector system to acclimate the furrowing depth and blade inclination. The trials were conducted in complexion soil with a humidity content of 18 and a constant operating speed of 5 km/ h. The results showed that the smart plow equipped with GPS and automatic depth adaptation technology achieved a 17.8 reduction in energy consumption and a 23.4 increase in depth uniformity compared to the traditional plow. Field productivity also increased by 19.7. These results indicate the effectiveness of smart systems in perfecting the performance of dig plows, which has a positive impact on the profitable and environmental aspects of husbandry. The study recommends the relinquishment of these systems in agrarian outfit, with the need to train drivers to insure effective performance.